High-capacity PANI / Ti3C2Tx composite material as well as preparation method and application thereof

By using PANI/Ti3C2Tx composite material as electrode material in capacitance deionization technology, nanosheet-like structures are formed through chemical etching and chemical oxidation polymerization reaction, solving the problems of low desalting capacity and poor stability of existing electrode materials, achieving high efficiency brine desalination and long-term stable desalination performance.

CN119480470APending Publication Date: 2025-02-18ZHEJIANG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411590437.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the existing capacitor deionization technology, the desalination capacity of electrode materials is low and the cycle stability is poor, making it difficult to meet the requirements of large-scale industrial production.

Method used

Using PANI/Ti3C2Tx composite material as the cathode for the hybrid capacitor deionization, HF is generated by reaction between LiF and HCl and chemical etching of Ti3C2Tx, selectively remove the Al layer, forming a nanosheet-shaped Ti3C2Tx precursor, and passing through C6H7N and (NH4)2S2O8 The chemical oxidation polymerization reaction forms PANI nanorods and is spontaneously assembled on the surface of Ti3C2Tx nanosheets.

Benefits of technology

The desalination capacity and stability of the composite material were significantly improved, with the desalination capacity reaching 79.4-116.3 mg/g, and there was no performance decline after 65 adsorption and desorption cycles, which was better than the performance of traditional carbon materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480470A_ABST
    Figure CN119480470A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of capacitive deionization, and discloses a high-capacity PANI / Ti3C2Tx composite material as well as a preparation method and application thereof. The preparation method comprises the following steps: carrying out a reaction on LiF, concentrated hydrochloric acid and Ti3AlC2, and carrying out ultrasonic treatment and re-centrifugation on the product to obtain a Ti3C2Tx nanosheet dispersion liquid; and adding sulfuric acid, C6H7N and (NH4) 2S2O8 into the Ti3C2Tx nanosheet dispersion liquid, carrying out mixing reaction, and carrying out washing and freeze-drying treatment on a product, so as to obtain the PANI / Ti3C2Tx composite material. The PANI nanorod is used for surface modification of the Ti3C2Tx nanosheet, so that the specific surface area of the composite material is increased, the structural stability of the composite material is improved, the PANI / Ti3C2Tx electrode material shows extremely high desalination capacity and excellent stability in salt water desalination, and the performance of the PANI / Ti3C2Tx electrode material is remarkably superior to that of a traditional carbon material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of capacitor deionization technology, and in particular to a high-capacity PANI / Ti3C2T x Composite material and preparation method and application thereof. Background Art

[0002] The water crisis is one of the biggest crises facing mankind in this century. In order to cope with the water crisis, vigorously developing water treatment technology has become an inevitable choice. Capacitive deionization (CDI) is a new water treatment technology that has emerged in recent years. It has the advantages of low energy consumption, high efficiency, pollution-free and recyclable, so it has great development prospects. The core of CDI technology is the electrode material. The existing electrode materials mainly include activated carbon, carbon aerogel, etc., but their ion capacity is limited and their performance cannot meet the requirements of large-scale industrial production. In order to overcome the limitations of desalination capacity and desalination rate of traditional electrode materials, researchers have turned their attention to new electrode materials with rich active sites and better performance, such as Faraday electrode materials with pseudocapacitive properties, titanium carbide (Ti3C2T x ), MoS2, Na2MnO4 and NaTi2(PO4)3, etc.

[0003] In the field of capacitive deionization, two-dimensional transition metal carbides / nitrides (MXene) have become an ideal choice to replace traditional electrode materials because of their high conductivity, adjustable interlayer spacing, rich surface functional groups, and excellent hydrophilicity. For example, the Chinese patent document with publication number CN118183957A discloses a Ti3C2T x Composite material, preparation method and application thereof, Ti3C2T coated on resin skeleton x After immersion in a cationic aqueous solution, the cation-induced Ti3C2T x Self-assembly, Ti3C2T x Loaded on resin, using Ti3C2T x The high electrochemical activity and strong mechanical properties of the resin make the composite material show better adsorption performance when used as an electrode material for capacitive deionization, but the maximum capacity is only 46.5 mg / g.

[0004] CN 106633051 A discloses a titanium carbide / polyaniline composite material and a preparation method thereof, wherein a two-dimensional layered nanomaterial MXeneTi3C2 is added to a hydrochloric acid solution and dispersed uniformly to obtain a Ti3C2 mixed solution; aniline is then added to the Ti3C2 mixed solution and dispersed uniformly to obtain a mixed solution; wherein the ratio of aniline to the two-dimensional layered nanomaterial MXene-Ti3C2 is (0.1-0.3) mL: (100-600) mg; a catalyst is added dropwise to the mixed solution A at 0-5°C, and the mixed solution is stirred and polymerized until the mixed solution gradually changes from a transparent solution to a uniform black solution, and then washed and dried to obtain a titanium carbide / polyaniline composite material. The PANI / Ti3C2 composite material is prepared by stirring at a low temperature of 0-5°C, which improves the problem that Ti3C2 is easily oxidized at high temperatures, but the desalination capacity of the material still needs to be improved.

[0005] Therefore, it is urgent to develop new Ti3C2T x Based on the composite electrode material, it promotes the more effective intercalation and loading of polyaniline on the Ti3C2 composite material. Summary of the invention

[0006] The present invention aims to solve the problems of low desalination capacity and poor cycle stability of existing electrode materials in capacitive deionization technology and provide a high-capacity PANI / Ti3C2T x Composite material and preparation method and application thereof, the composite material is used as active material to prepare PANI / Ti3C2T x As the cathode of hybrid capacitive deionization, it exhibits excellent desalination capacity and good stability.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A high-capacity PANI / Ti3C2T x A method for preparing a composite material comprises the steps of:

[0009] Step 1: LiF and concentrated hydrochloric acid are mixed under ice bath, and Ti3AlC2 is added thereto for reaction. The product is centrifuged, washed, dispersed in water, and subjected to ultrasonication and centrifugation to obtain Ti3C2T x Nanosheet dispersion; ultrasonic power of 100-300W, ultrasonic time of 2-4h; re-centrifugal speed of 3000-4000rpm, re-centrifugal time of 1-2h;

[0010] Step 2: Ti3C2T x Sulfuric acid, C6H7N and (NH4)2S2O8 were added to the nanosheet dispersion for mixed reaction, and the product was washed and freeze-dried to obtain the PANI / Ti3C2T x Composite materials.

[0011] The PANI / Ti3C2T ... x The preparation principle of the electrode material is: HF produced by the reaction of LiF and HCl reacts with Ti3C2T x Chemical etching is performed to selectively remove the Al layer. - The high reactivity of ions with Al causes the Al-C chemical bond to break, while the stronger Ti-C bond remains unaffected. Subsequently, the tightly stacked Ti3C2T x The sheets are separated and freeze-dried to remove the interlayer water molecules, and finally a two-dimensional nanosheet Ti3C2T with an increased specific surface area and a good pore structure is obtained. x Precursor. Due to the presence of surface functional groups, nanosheet Ti3C2T x Negatively charged.

[0012] At the same time, C6H7N undergoes chemical oxidation polymerization under the action of (NH4)2S2O8 to form positively charged PANI. x Spontaneous assembly under electrostatic interaction in porous Ti3C2T x The nanosheets grow uniformly on the surface. Meanwhile, the PANI nanorods x Surface modification of nanosheets for two-dimensional Ti3C2T x Nanosheets play a supporting role. The structure of two-dimensional nanosheets is more stable and not easy to stack, which is conducive to the multiple insertion and extraction of ions during salt water desalination, increasing the specific surface area of ​​the composite material and improving the structural stability of the composite material. The desalination capacity of the composite material is greatly improved, which is significantly better than the performance of traditional carbon materials. This research not only expands the application potential of capacitive deionization technology, but also provides a new path for the development of high-efficiency materials to replace traditional carbon electrodes.

[0013] The mass ratio of Ti3AlC2 and LiF in step 1 is (0.5-1) g: (0.8-1.5) g. When the content of LiF is too low, the etching reaction F - The concentration of ions is insufficient, the etching reaction slows down, the Al layer is not completely peeled off, and the etching effect is not significant, resulting in the Ti3C2T x The stratification is not obvious, and the active sites of the composite material are not fully exposed. However, too high a LiF content will cause excessive etching, resulting in the Ti3C2T x Too many structural defects are generated on the surface of the nanosheets, which hinder the ion transport in the desalination process and ultimately reduce the desalination performance of the material.

[0014] The mass volume ratio of LiF and concentrated hydrochloric acid in step 1 is (0.8-1.5) g: (5-15) ml.

[0015] The mixing time in step 1 is 10-30 min;

[0016] In step 1, the reaction temperature is 30-50° C., the reaction time is 20-28 h, the centrifugal speed after the reaction is completed is 4000-11000 rpm, and the centrifugal time is 5-15 min.

[0017] The purpose of centrifugation after ultrasound in step 1 is to separate the effectively exfoliated nanosheets. If the rotation speed is too low, the desired Ti3C2T x Nanosheets, the rotation speed is too high, the obtained Ti3C2T x The product is impure and contains Ti3AlC2 that was not successfully etched.

[0018] Step 2 Ti3C2T x The ratio of nanosheet dispersion, sulfuric acid, C6H7N and (NH4)2S2O8 is (5-12.5) ml: (0.1-0.3) mol: (0.3-0.5) ml: (0.5-1) g;

[0019] The Ti3C2T x Ti3C2T in nanosheet dispersion x The concentration is 7.5~12.5mg / ml.

[0020] This will directly affect the Ti3C2T x The morphology of PANI on the nanosheet surface hinders the exposure of active sites and ion transport in the desalination process of the composite material.

[0021] The molar ratio of C6H7N to (NH4)2S2O8 is 1-2:1. (NH4)2S2O8 acts as an oxidant to participate in the chemical oxidation polymerization reaction of C6H7N to generate PANI. The content of the oxidant and the concentration of the C6H7N monomer will directly affect the conductivity of PANI, and then affect the PANI / Ti3C2T x desalination performance.

[0022] The molar concentration of sulfuric acid in step 2 is 1-3 mol / L. Low acidity will lead to insufficient protonation, thereby reducing the conductivity of PANI. On the contrary, appropriate acidity can effectively improve the conductivity of PANI, accelerate ion transfer and charge transfer, and increase the PANI / Ti3C2T x desalination capacity.

[0023] The reaction time in step 2 is 9-29h.

[0024] The present invention provides a high-capacity PANI / Ti3C2T prepared by the preparation method. x Composite materials.

[0025] The PANI / Ti3C2T x Nanorod-shaped PANI in the composite material is loaded on Ti3C2T x Nanosheet surface;

[0026] The diameter of the nanorod-shaped PANI is 35-45 nm, and the length is 400-700 nm; the Ti3C2T x The size of the nanosheets is 3 to 10 um.

[0027] The present invention also provides the high-capacity PANI / Ti3C2T x Application of composite materials in capacitive deionization.

[0028] The high-capacity PANI / Ti3C2T x The composite material was used as the cathode of HCDI and showed ultra-high desalination capacity and excellent long-term stability in the desalination test. x Composite materials are used as cathode materials. PANI / Ti3C2T x The materials had a desalination capacity of 79.4-116.3 mg / g.

[0029] In 500ppm NaCl solution, after applying 1.2V voltage, PANI / Ti3C2T x The material exhibited an ultra-high desalination capacity of 91.6 mg / g and showed no performance degradation after 65 adsorption-desorption cycles.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] In the present invention, PANI nanorods are used to bind Ti3C2T x The surface modification of nanosheets increases the specific surface area of ​​the composite material and improves the structural stability of the composite material, making PANI / Ti3C2T x The electrode material exhibits extremely high desalination capacity and excellent stability in salt water desalination, significantly outperforming the performance of traditional carbon materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 PANI / Ti3C2T prepared in Example 1 x Scanning electron microscopy images of the composite materials.

[0033] Figure 2 This is a cycle performance diagram of the materials prepared in Example 1 and Comparative Examples 1-2 in Application Example 1.

[0034] Figure 3 For different Ti3C2Tx Dosage of PANI / Ti3C2T x Figure 2. Desalination performance of the composite material.

[0035] Figure 4 PANI / Ti3C2T with different polymerization times in Application Example 3 x Figure 2. Desalination performance of the composite material. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0037] The raw materials used in the following specific embodiments are all purchased from the market.

[0038] Example 1

[0039] Step 1, take 10mL 12M concentrated hydrochloric acid in a 50mL centrifuge tube, add 1.1g LiF under stirring, and stir thoroughly for 20min. Measure 0.7g Ti3AlC2 and slowly add it to the above solution, stir for 20min to mix the reactants evenly, start heating after cooling to room temperature, and etch the reaction at 40℃ for 24h. After the reaction, the solution is centrifuged at 9000rpm for 5min, and repeatedly centrifuged and washed with deionized water until the pH of the supernatant is 5-7, and the precipitate is retained. The above centrifuged precipitate is dispersed in 40mL deionized water, ultrasonicated at room temperature for 3h, and the resulting suspension is centrifuged at 3500rpm for 1h, and the clear liquid is retained.

[0040] Step 2: Measure 100 mL of 1M dilute sulfuric acid in a beaker and add 7.5 mL of the prepared Ti3C2T x The precursor dispersion was then added with 0.4 mL C6H7N and 700 mg (NH4)2S2O8, and the mixture was reacted in an ice bath for 24 h. The precipitate was washed with deionized water and collected by centrifugation and freeze-dried to obtain PANI / Ti3C2T x Composite material, denoted as PANI / Ti3C2T x -75.

[0041] PANI / Ti3C2T prepared in this example x The composite material was analyzed by scanning electron microscope. Figure 1 As shown. Figure 1 It can be seen that the nanorod-like PANI is present in Ti3C2Tx The nanosheets grow evenly on the surface, and the diameter of the nanorod-shaped PANI is 35-45 nm and the length is 400-700 nm. x The size of the nanosheets is 3 to 10 um.

[0042] Comparative Example 1

[0043] According to the process of Example 1, step (2) is not performed, and step (1) obtains Ti3C2T x Ti3C2T was obtained after freeze-drying the precursor dispersion. x powder.

[0044] Comparative Example 2

[0045] According to the process of Example 1, step (1) is not performed, and Ti3C2T is not added in step (2). x Precursor dispersion to obtain PANI.

[0046] Example 2

[0047] The process of Example 1 is the same as that of Example 1, except that in step (2), the amounts of sulfuric acid, C6H7N and (NH4)2S2O8 are kept unchanged, and Ti3C2T x The volumes of the precursor dispersions were replaced with 5 ml, 10 ml, and 12.5 ml, corresponding to PANI / Ti3C2T x -50, PANI / Ti3C2T x -100, PANI / Ti3C2T x -125.

[0048] Example 3

[0049] The process of Example 1 is followed, except that in step (2), the ice bath polymerization time is 9 h, 14 h, 19 h, and 29 h, to obtain composite materials with different polymerization times.

[0050] Application Example 1

[0051] The experiment used an HCDI device, the electrolyte was a 500ppm NaCl solution, and the negative electrode material was the PANI / Ti3C2T prepared in Example 1 and Comparative Examples 1-2. x Composite material. The active material, carbon black and polyvinylidene fluoride were mixed and ground evenly in a mass ratio of 8:1:1, and then dispersed in N-methylpyrrolidone to prepare ink. 2The loading amount was applied on carbon paper. The sample was dried at 60°C for 12 hours to obtain the cathode of HCDI. Similarly, the above active material was replaced with commercial activated carbon to obtain the anode. In the experiment, a constant voltage of 0.9 to 1.5V was applied to both ends of the HCDI device, and the target ions began to adsorb. The conductivity of the electrolyte was monitored using a conductivity meter to measure the desalination performance of the electrode material.

[0052] After the adsorption experiment, a short circuit was used to start the desorption experiment. When the conductivity reading of the electrolyte returned to the initial value and stabilized, it indicated that the desorption process was completed, and an adsorption / desorption cycle was completed. At a constant voltage of 1.2V, the salt solution continuously flowed into the HCDI device at a fixed flow rate through a peristaltic pump, and multiple adsorption / desorption cycle experiments were performed. The changes in conductivity in each cycle were monitored to evaluate the desalination stability of the electrode material.

[0053] like Figure 2 As shown, compared with PANI and Ti3C2T x , PANI / Ti3C2T x The desalination capacity of the electrode material remained at 91.6 mg / g after 65 adsorption / desorption cycles, which was significantly better than that of PANI and Ti3C2T3 when used alone. x electrode. It shows that PANI / Ti3C2T x Electrode materials have broad application prospects in HCDI desalination applications.

[0054] Application Example 2

[0055] According to the process of Application Example 1, the materials prepared in Example 1 and Example 2 were tested in the application example. The results are as follows: Figure 3 As shown, 5ml, 7.5ml, 10ml, and 12.5ml of feed correspond to PANI / Ti3C2T x -50, PANI / Ti3C2T x -75, PANI / Ti3C2T x -100, PANI / Ti3C2T x -125. Figure 3 It can be seen that when a constant voltage of 1.2 V is applied, the PANI / Ti3C2T prepared in Example 1 x -75 showed the highest desalination capacity of 91.6 mg / g. PANI / Ti3C2T x -50, PANI / Ti3C2T x -100, PANI / Ti3C2T x The corresponding desalination capacities of -125 are 32.0 mg / g, 82.8 mg / g, and 61.1 mg / g, respectively.

[0056] Application Example 3

[0057] According to the process of Application Example 1, the materials prepared in Example 1 and Example 3 were tested in the application example. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that the composite material prepared in Example 1 with a polymerization time of 24 h exhibits the highest desalination capacity of 91.6 mg / g. The corresponding capacities of the materials with polymerization times of 9 h, 14 h, 19 h, and 29 h are 49.6 mg / g, 51.3 mg / g, 78.4 mg / g, and 85.3 mg / g, respectively.

Claims

1. A high-capacity PANI / Ti3C2T x A method for preparing a composite material, characterized in that: Includes steps: Step 1: LiF and concentrated hydrochloric acid are mixed under ice bath, and Ti3AlC2 is added thereto for reaction. The product is centrifuged, washed, dispersed in water, and subjected to ultrasonication and centrifugation to obtain Ti3C2T x Nanosheet dispersion; ultrasonic power of 100-300w and ultrasonic time of 2-4h; re-centrifugal speed of 3000-4000rpm and re-centrifugal time of 1-2h; Step 2: Ti3C2T x Sulfuric acid, C6H7N and (NH4)2S2O8 were added to the nanosheet dispersion for mixed reaction, and the product was washed and freeze-dried to obtain the PANI / Ti3C2T x Composite materials.

2. The high capacity PANI / Ti3C2T3 according to claim 1 x A method for preparing a composite material, characterized in that: In step 1, the mass ratio of Ti3AlC2 and LiF is (0.5-1) g:(0.8-1.5) g, and the mass volume ratio of LiF and concentrated hydrochloric acid is (0.8-1.5) g:(5-15) ml.

3. The high capacity PANI / Ti3C2T3 according to claim 1 x A method for preparing a composite material, characterized in that: The mixing time in step 1 is 10-30 minutes.

4. The high capacity PANI / Ti3C2T3 according to claim 1 x A method for preparing a composite material, characterized in that: In step 1, the reaction temperature is 30-50° C., the reaction time is 20-28 h, the centrifugal speed after the reaction is completed is 4000-11000 rpm, and the centrifugal time is 5-15 min.

5. The high capacity PANI / Ti3C2T3 according to claim 1 x A method for preparing a composite material, characterized in that: Step 2 Ti3C2T x The ratio of nanosheet dispersion, sulfuric acid, C6H7N and (NH4)2S2O8 is (5-12.5) ml: (0.1-0.3) mol: (0.3-0.5) ml: (0.5-1) g; The Ti3C2T x Ti3C2T in nanosheet dispersion x The concentration is 7.5~12.5mg / ml.

6. The high capacity PANI / Ti3C2T3 according to claim 1 x A method for preparing a composite material, characterized in that: The reaction time in step 2 is 9-29h.

7. A high-capacity PANI / Ti3C2T prepared by the preparation method according to any one of claims 1 to 6 x Composite materials.

8. The high capacity PANI / Ti3C2T3 according to claim 7 x A composite material, characterized in that The PANI / Ti3C2T x Nanorod-shaped PANI in the composite material is loaded on Ti3C2T x Nanosheet surface; The diameter of the nanorod-shaped PANI is 35-45 nm, and the length is 400-700 nm; the Ti3C2T x The size of the nanosheets is 3 to 10 um.

9. The high-capacity PANI / Ti3C2T3 according to claim 7 or 8 x Application of composite materials in capacitive deionization.

10. The high capacity PANI / Ti3C2T3 according to claim 9 x The application of the composite material in capacitive deionization is characterized in that: The PANI / Ti3C2T x Composite materials are used as cathode materials. PANI / Ti3C2T x The materials had a desalination capacity of 79.4-116.3 mg / g.

Citation Information

Patent Citations

  • Rodlike polyaniline load modified titanium carbide and low-temperature preparation method thereof

    CN106633050A

  • MXene-polyaniline composite material and preparation method thereof

    CN106750277A

  • Preparation method of high-capacity linear supercapacitor electrode based on MXene / PANI

    CN111223687A

  • Preparation method of polyaniline / MXene composite fabric and application of polyaniline / MXene composite fabric in printing and dyeing wastewater treatment

    CN112064363A